Optimised editing of variable data documents via partial re-evaluation - Ollis, James A .J. (2011)
With the advent of digital printing presses and the continued development of associated technologies, variable data printing (VDP) is becoming more and more common. VDP allows for a series of data instances to be bound to a single template document in order to produce a set of result document instances, each customized depending upon the data provided. As it gradually enters the mainstream of digital publishing there is a need for appropriate and powerful editing tools suitable for use by creative professionals. This thesis investigates the problem of representing variable data documents in an editable visual form, and focuses on the technical issues involved with supporting such an editing model.